Fiscal Policy and Monetary Policy in Overcoming Poverty in Indonesia - Syaiful Ma'ruf (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
This study aims to analyze the role of fiscal policy and monetary policy in overcoming poverty in Indonesia as one of the government's efforts to address economic problems. The type of research method used is a qualitative descriptive research method by preparing, collecting, and analyzing data. The collected data is then processed through three stages, namely data reduction, data presentation, and conclusion withdrawal. The results of this study show that poverty is a problem faced by all countries, especially in developing and lagging countries. The problem of poverty is multidimensional caused by many factors that are not only the domain of economics but also political, social, cultural, and other social systems. Fiscal policy and monetary policy greatly helped to lower the poverty rate in Indonesia. With fiscal policy and monetary policy, it can help the government solve one of the problems of the Indonesian economy. Although it did not completely resolve, it was able to reduce the poverty rate in Indonesia to remain on the normal line so that it did not affect economic growth and development in Indonesia.